Climatic and ecological factors responsible for distribution of Phlebotomine sandflies and occurrence of cutaneous leishmaniasis, in Himachal Pradesh, India - Suman Lata; Gaurav Kumar; Bharat Bhakuni; Sandhya Kumari; Ramesh C Dhiman (Journal of Vector Borne Diseases)
Background & objectives: Subalpine valley along the Sutlej River has been identified as an endemic focus for cutaneous leishmaniasis (CL) in Himachal Pradesh (H.P.) state in India. The present study was undertaken with the aim to find out the climatic and ecological determinants responsible for distribution of sandflies and occurrence of CL in Himachal Pradesh. Methods: Collections of sandflies were made in the Shimla, Kullu, and Kinnaur districts of H.P. during 2017 and 2019. The climatic data were procured from Indian Meteorological centre, Shimla (H.P). The satellite images (Indian remote sensing satellite (IRS)-Linear imaging self-scanner (LISS)-IV sensor multispectral data) having resolution of 5.8m were procured from National Remote Sensing Centre, Hyderabad, India. The relationship between the incidence of CL and Land Use was analysed. Results: A total of 332 sandflies were collected. The transmission of CL was favoured by temperatures exceeding 20°C over a period of six months, specifically from April to September. The valley with an elevation ranging between 1000 to 1250 meters reported 90% of the CL cases. The correlation between CL incidence and land use patterns revealed a notable rise in barren land (8%) and scrub land (5%) from 2013 to 2017. Interpretation & conclusion: The findings reveals that specific meteorological conditions and land cover play a significant role in determining the presence of sandflies in Himachal Pradesh. To effectively control CL, it is recommended to implement control programs primarily between June and September, focusing particularly on regions with elevations ranging from 1000 to 1250 meters.